Research on the failure mechanism of the high-speed train bearing steel under static load failure. (July 2022) - Ma, Ze-ming; Dong, Shao-kang; Zhu, Hao; Cao, Ya-bin; Wang, Chen-ji; Cao, Zhi-long; Yang, Shao-pu
Highlights: Microstructure of bearing outer ring Characterized by various means. Three crack nucleation sites appear after tensile unloading. The initiation and propagation of crack was monitored by in-situ tension with the increasing of stress. Bainite colony (Prior austenite) leads to quasi cleavage fracture as the weakest link. Abstract: Bearing plays an important role in operation safety as the key component of high-speed train. The service life is affected by the fracture behavior of bearing during operation seriously. In this paper, the MTS universal testing machine was used to carry out tensile test and tension-unloading test on the sample of the bearing outer ring. On this basis, the fracture process was dynamically monitored by in-situ tensile test. The stress state of the sample during tensile process was calculated by the finite element software ABAQUS. The results show that the microstructure is composed of lower bainite, (Fe, Cr)3 C carbides and a small amount of residual austenite. The ultimate strength of outer ring is 2.3GPa. Compared with the center of the sample, the stress triaxiality on the surface is low and the shear stress is high relatively, reinforcing the local plastic deformation. Microcracks are the main damage forms of bearing outer ring. The microcracks nucleate in the three sites, which are the boundary of bainite colony, between the bainite lamellae and around carbide. The bainite colony is the weakest link of the bearing. A large number of microcracks nucleate on the boundary of bainite colony. Under the action of tensile loading, the microcracks propagate along the boundary of bainite colony. With the increasing of load, the cracks propagate unsteadily and lead to the quasi-cleavage fracture of the sample.